Why the Level-Free Forced-Choice Binary Measure of Brand Benefit Beliefs Works So Well. (March 2015) - Rossiter, John R.; Dolnicar, Sara; Grün, Bettina
The level-free version of the Forced-Choice Binary measure of brand benefit beliefs was introduced in a recent article in IJMR (Dolnicar et al. 2012) and was shown to yield more stable – hence more reliable and trustworthy – results than the shorter 'Pick-Any' measure and the longer '7-Point Scale' measure. The aims of the present article are (1) to explain how and why the Level-Free Forced-Choice Binary measure works so well, and (2) to point out its advantages over other belief measure formats - advantages that, importantly, include prevention of all forms of response bias.